Quantity not sufficient rates and delays in sweat testing in US infants with cystic fibrosis. Issue 11 (25th August 2020) - McColley, Susanna A.; Elbert, Alexander; Wu, Runyu; Ren, Clement L.; Sontag, Marci K.; LeGrys, Vicky A.
Abstract: Background: Diagnostic sweat testing is required for infants with positive newborn‐screening (NBS) tests for cystic fibrosis (CF). Infants have "quantity not sufficient" (QNS) sweat volumes more often than older children. A comprehensive study of QNS sweat volumes in infants has not previously been reported. Methods: We surveyed US CF Centers to obtain QNS rates in all infants who had sweat testing at under 14 days and under 3 months of age. We then calculated QNS rates reported to the Cystic Fibrosis Foundation Patient Registry (CFFPR) 2010‐2018 in 10‐day increments from 1 to 60 days of life. We compared QNS sweat test rates in preterm (<37‐weeks gestational age) vs term infants. We assessed age at sweat test and proportion of infants who did not have a sweat test reported by 60 days of age. Results: Thirty‐nine of 144 (27%) of CF Centers reported a mean QNS rate of 10.5% (range, 0‐100) in infants 14‐days‐old or younger. CFFPR data showed the highest QNS rates in the youngest infants and in those born before 37 weeks of gestation. The median age at sweat testing decreased over time, but more than 22% of infants did not have a sweat test reported by 60 days. Conclusion: Higher QNS rates are seen in the youngest infants with CF, but more than 80% of infants younger than 2 weeks of age have adequate sweat volumes. Sweat testing should not be delayed in infants with a positive CF NBS test.